PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BADAN INTELIJEN NEGARA DAERAH (BINDA) KEPULAUAN RIAU - Shafiq, Dhio; Hamta, Firdaus; Santoso, Cahyo Budi (LPPM Universitas Ibnu Sina, 2021)
This study aims to analyze the influence of leadership and competence on employee performance with job satisfaction as a variable that intervenes in the Regional State Intelligence Agency (Binda) Kepri. This study uses quantitative methods and uses a questionnaire with a Likert scale with a sample of 74 respondents. This research uses model analysis and hypothesis testing using partial test and simultaneous F test. The results showed (1) Leadership has a positive and significant effect on Job Satisfaction of Binda Kepri employees (2) Leadership has a positive and significant effect on the performance of Binda Kepri employees. (3) Competence has a positive and significant effect on job satisfaction of Binda Kepri employees (4) Competence has a positive and significant effect on employee performance of Binda Kepri. (5) Employee job satisfaction has a positive and significant effect on employee performance Binda Kepri (6) Leadership has a positive and significant effect on employee performance through Binda Kepri job satisfaction (7) Competence has a significant and significant effect on employee performance through Binda Kepri job satisfaction.